Respuesta :

Answer:

Simplifying

Ax + 3 = 8x + b

Reorder the terms:

3 + xA = 8x + b

Reorder the terms:

3 + xA = b + 8x

Solving

3 + xA = b + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.

3 + -8x + xA = b + 8x + -8x

Combine like terms: 8x + -8x = 0

3 + -8x + xA = b + 0

3 + -8x + xA = b

Add '-3' to each side of the equation.

3 + -8x + -3 + xA = -3 + b

Reorder the terms:

3 + -3 + -8x + xA = -3 + b

Combine like terms: 3 + -3 = 0

0 + -8x + xA = -3 + b

-8x + xA = -3 + b

Reorder the terms:

3 + -1b + -8x + xA = -3 + b + 3 + -1b

Reorder the terms:

3 + -1b + -8x + xA = -3 + 3 + b + -1b

Combine like terms: -3 + 3 = 0

3 + -1b + -8x + xA = 0 + b + -1b

3 + -1b + -8x + xA = b + -1b

Combine like terms: b + -1b = 0

3 + -1b + -8x + xA = 0

The solution to this equation could not be determined.

Step-by-step explanation:

ACCESS MORE